The Antecedents Factors of Entrepreneurship among Female University Students in Indonesia - Calista, Felisha; Patricia, Patricia (Universitas Pelita Harapan, 2023)
Women are starting and running successful businesses around the world, including in Indonesia. Women entrepreneurs are becoming a major force in the global economy and are seen as key contributors to economic growth and job creation. However, women still encounter obstacles that hinder their ability to compete with men despite their innovative ideas. Therefore, in this research, the researcher explains the effects of these entrepreneurial factors on female university students who have the intention to become entrepreneurs. This research examines the impact of various factors on the female entrepreneurial intention of 340 female university students. For example, the effect of entrepreneurial self-efficacy and perceived behavioral control on female entrepreneurial intention. In this research, the researcher presents a research model which consists of Supporting Condition, Entrepreneurial Self-Efficacy, Perceived Behavioral Control, and Female Entrepreneurial Intention with Female Entrepreneurial Intention as the dependent variable, the researcher’s findings support the hypotheses that these factors really do have impact on female university students’ entrepreneurial intention in Indonesia.